Analisis Pengujian Otomatis Antarmuka Web Pada Formulir Jotform Menggunakan Cypress - Sigit Wijanarko (Jurnal Sosial Teknologi, 2026)
Web interface testing is a critical stage in ensuring the functionality of web-based applications, including those delivered through Software as a Service (SaaS) platforms that provide online form services. Jotform is a widely used SaaS platform for building online forms; however, its dynamic characteristics, use of iframes, and limited access to source code can make manual testing inefficient and difficult to reproduce. Therefore, end-to-end automated testing represents a relevant approach for validating the functionality of such web form interfaces. This study aims to analyze the application of the Cypress framework for automated web interface testing on SaaS-based Jotform forms. The research employs a quantitative descriptive approach, with the research object consisting of a simulated form designed using multi-page features, conditional logic, field validation, and URL prefill mechanisms. Testing was conducted by repeatedly executing a single primary scenario, namely successful form submission, under the same testing environment. The analyzed variables include test execution time, test stability, and test script complexity. The results indicate that Cypress is able to execute automated web interface tests on Jotform forms consistently, with relatively stable execution times and no failures observed during repeated test runs. In addition, test script complexity increases as additional handling for dynamic elements and conditional validation is introduced. These findings suggest that Cypress can be considered a reliable automated testing framework for testing web interfaces of SaaS-based online forms.